2019
DOI: 10.3390/nu11081763
|View full text |Cite
|
Sign up to set email alerts
|

Using Food Models to Enhance Sugar Literacy among Older Adolescents: Evaluation of a Brief Experiential Nutrition Education Intervention

Abstract: Adolescent diets high in sugar are a public health concern. Sugar literacy interventions have changed intake but focused more on children, adults, and early adolescents and on sugar sweetened beverages rather than total sugar consumption. Food models are an efficacious experiential learning strategy with children. This study assessed the impact of two 45 min nutrition lessons using food models on adolescents’ sugar literacy. Classes (n = 16) were randomized to intervention or control with knowledge, label read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Specifically, dietary education can promote the adequate behavior of adolescents in the face of their inadequate diet [7]. In line with this, it has been observed that youths follow a diet with a high sugar content, which is detrimental to their health [8].…”
Section: Introductionmentioning
confidence: 93%
“…Specifically, dietary education can promote the adequate behavior of adolescents in the face of their inadequate diet [7]. In line with this, it has been observed that youths follow a diet with a high sugar content, which is detrimental to their health [8].…”
Section: Introductionmentioning
confidence: 93%
“…media campaigns (6,137,(162)(163)(164)(165)(166)(167)(168)(169)(170) , community education (171)(172)(173)(174)(175)(176)(177)(178) and education in schools and childcare centres (179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196) on the harms of excess added sugar consumption. Of the studies exploring this policy action (n 39), only eight (Table 4) addressed the impact that education interventions to reduce added sugar intake may have on NNS consumption and levels in the food supply.…”
Section: Education Interventions Education-based Interventions Includedmentioning
confidence: 99%
“…In this sense, the fact of being overweight or obese can generate serious public health problems [46], affecting the increase in the mortality rate [47]. In the educational field, the assimilation of good eating habits in students [48] acquires great relevance, given that the actions developed through transversal treatment or nutritional education programs promote adequate dietary guidelines [49,50] while avoiding bad praxis, among which is the intake of sugars and other substances harmful to health [51,52], especially in those people who have various diseases, such as diabetes or cardiovascular problems [53,54].…”
Section: Dietary Habits As a Factor Of Health And Development In Schomentioning
confidence: 99%